TaÊ¼thÄ«r WasÄ«lah Al-Kutub Al-Mujassimah Al-Mutaá¸¥arrikah Ê»alÃ¡ IstÄ«Ê¿Äb Al-MufradÄt LadÃ¡ á¹¬ullÄb Al-Madrasah Al-IbtidÄÊ¼Ä«yah Al-IslÄmÄ«yah Al-á¸¤ukÅ«mÄ«yah Bukittinggi - Annisa, Ayu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The problems in this research are student's comprehension of Arabic vocabulary is low. In addition, the teacher did not use the fun and varied teaching media when teaching. The aims of this research is: 1) To find out the difference in the comprehension of Arabic vocabulary between students who learn using Pop Up Books media and students who learn using whiteboard, 2) To know the effect of the Pop Up Books media on the comprehension of Arabic vocabulary for the 3rd grade students at the Goverment Islamic Elementary School Bukittinggi. This research is experimental research means quasi-experimental by type non equivalent control grup. The population is all 3rd grade students and the sampling technique is cluster sampling. The data collection tools used are test, observation and interview. The result of the research are: 1) There is a difference in the comprehension of Arabic vocabulary between students who learn using Pop Up Books media and students who learn using whiteboard, 2) There is an effect of the Pop Up Books media on the comprehension of Arabic vocabulary for the 3rd grade students at the Goverment Islamic Elementary School Bukittinggi because in Independent Sample t-Test, the researcher obtained a score of tcount>ttable (2,257>2,009).Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù†Ø®ÙØ¶. Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ø°Ù„ÙƒØŒ Ù„Ù… ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ù…Ø¯Ø±Ù‘Ø³Ø© Ø§Ù„ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„Ù…Ù…ØªØ¹Ø© ÙˆØ§Ù„Ù…ØªÙ†ÙˆØ¹Ø© Ø¹Ù†Ø¯ Ø§Ù„ØªØ¹Ù„ÙŠÙ…. Ø£Ù‡Ø¯Ø§Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ: 1) Ù„Ù…Ø¹Ø±ÙØ© ÙØ±Ù‚ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨ÙŠÙ† Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙƒØªØ¨ Ø§Ù„Ù…Ø¬Ø³Ù…Ø© Ø§Ù„Ù…ØªØØ±ÙƒØ© (Pop Up Books) ÙˆØ§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø³Ø¨ÙˆØ±Ø©ØŒ 2) Ù„Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙƒØªØ¨ Ø§Ù„Ù…Ø¬Ø³Ù…Ø© Ø§Ù„Ù…ØªØØ±ÙƒØ© (Pop Up Books) Ø¹Ù„Ù‰ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù„Ø« ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø¨ÙˆÙƒÙŠØª ØªÙ†Ø¬ÙŠ. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ ÙŠØ¹Ù†ÙŠ Ø´Ø¨Ù‡ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØ© Ø¨Ø§Ù„Ù†ÙˆØ¹ Ù…Ø¬Ù…ÙˆØ¹Ø© Ø§Ù„Ø¶Ø§Ø¨Ø· ØºÙŠØ± Ù…ØªÙƒØ§ÙØ¦Ø©. ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹ Ù„Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù„Ø« ÙˆØªÙ‚Ù†ÙŠØ© Ø£Ø®Ø° Ø§Ù„Ø¹ÙŠÙ†Ø§Øª Ù‡ÙŠ Cluster Sampling. Ø£Ø¯ÙˆØ§Øª Ù„Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© Ù‡ÙŠ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± ÙˆØ§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©. Ø£Ù…Ø§ Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ: 1) ÙŠÙˆØ¬Ø¯ ÙØ±Ù‚ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨ÙŠÙ† Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙƒØªØ¨ Ø§Ù„Ù…Ø¬Ø³Ù…Ø© Ø§Ù„Ù…ØªØØ±ÙƒØ© (Pop Up Books) ÙˆØ§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ø°ÙŠÙ† ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø³Ø¨ÙˆØ±Ø©ØŒ 2) ÙŠÙˆØ¬Ø¯ ØªØ£Ø«ÙŠØ± ÙˆØ³ÙŠÙ„Ø© Ø§Ù„ÙƒØªØ¨ Ø§Ù„Ù…Ø¬Ø³Ù…Ø© Ø§Ù„Ù…ØªØØ±ÙƒØ© (Pop Up Books)Â Ø¹Ù„Ù‰ Ø§Ø³ØªÙŠØ¹Ø§Ø¨ Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù„Ø« ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø¨ÙˆÙƒÙŠØª ØªÙ†Ø¬ÙŠ Ù„Ø£Ù† ÙÙŠ Ø§Ø®ØªØ¨Ø§Ø± Independent Sampel t-Test ØØµÙ„Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¹Ù„Ù‰ Ø¯Ø±Ø¬Ø©